Study on prediction of the effects of design and operating parameters on NOx emissions from a leanburn natural gas engine - Kesgin, U (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
With increasingly strict emission regulations, engine manufacturers are developing new strategies and technologies to reduce exhaust gas emissions. Thus, exhaust gas emission limits and test procedures for internal combustion engines, as well as for other combustion systems, have had a market impact upon the development of the engines and systems. Because of the requirement for good fuel economy and low NOx emissions that dominate engine design practice, reducing NOx emissions requires a detailed understanding of the chemical pathways for emission formation. Over the past several years, an increasing number of models for the formation of exhaust gas emissions have been implemented. In recent years, both environmental and economic concerns have stimulated a strong interest in using natural gas for internal combustion engines. One of the reasons to use natural gas as the fuel in engines is the ability to produce relatively little NOx. This paper deals with the effects of design and operational parameters on the NOx emissions of a turbocharged natural gas engine. Within the framework of a detailed research and development project in cooperation with university and industry, a gas engine series used in combined power plants has been optimised regarding power, efficiency and emissions. Since an evaluation of the emission behaviour is increasingly important, the nitrogen oxide emission and its dependence on engine operational and geometrical conditions were investigated by using a zero dimensional reaction kinetic model as well as experimental studies. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: NOx modelling; natural gas engine; operational and design parameters; COMBUSTION; Thermodynamics; Energy & Fuels; Mechanics